Cyclic AMP Recruits a Discrete Intracellular Ca(2+) Store by Unmasking Hypersensitive IP(3) Receptors - Konieczny, Vera (Cell Rep, 2017)
Inositol 1,4,5-trisphosphate (IP(3)) stimulates Ca(2+) release from the endoplasmic reticulum (ER), and the response is potentiated by 3′,5′-cyclic AMP (cAMP). We investigated this interaction in HEK293 cells using carbachol and parathyroid hormone (PTH) to stimulate formation of IP(3) and cAMP, respectively. PTH alone had no effect on the cytosolic Ca(2+) concentration, but it potentiated the Ca(2+) signals evoked by carbachol. Surprisingly, however, the intracellular Ca(2+) stores that respond to carbachol alone could be both emptied and refilled without affecting the subsequent response to PTH. We provide evidence that PTH unmasks high-affinity IP(3) receptors within a discrete Ca(2+) store. We conclude that Ca(2+) stores within the ER that dynamically exchange Ca(2+) with the cytosol maintain a functional independence that allows one store to be released by carbachol and another to be released by carbachol with PTH. Compartmentalization of ER Ca(2+) stores adds versatility to IP(3)-evoked Ca(2+) signals.